Effect of different DOM components on arsenate complexation in natural water. (1st February 2021) - Zhang, Fan; Li, Xue; Duan, Lizeng; Zhang, Hucai; Gu, Wen; Yang, Xingxin; Li, Jingping; He, Sen; Yu, Jie; Ren, Meijie
Abstract: Dissolved organic matter (DOM) and dissolved ions are two integral parameters to affect the environmental fate of As in different ways. Numerous studies chose surrogate of DOM, humic substances (HSs), to investigate the As complexation behavior. However, microbial secretion (protein and polysaccharide) was also considered for a great proportion in surface aquatic system, and its effect was still not fully understood. The present research distinguished the As complexation behavior with different DOM components (HSs, protein, polysaccharide and synthetic organic matter) in natural and simulated water samples. The results indicated that different DOM components exhibited various binding capacities for As. HSs showed the strongest affinity for As, followed by long-chain compounds (polysaccharide and synthetic organic matter) and proteins. In water source, HSs were probably the primary parameter for As complexation. In eutrophic water system, however, polysaccharide maybe the main DOM component to bind As. Cationic bridge function was prone to occur in the presence of HSs, but not observed in the presence of protein. PO4 3− competed for binding sites with As, consequently decreasing the As complexation with all the DOM components. The research implied that a comprehensive and meticulous analyses of DOM fractions and coexist ions are the prerequisite to understanding the behavior of As (or other pollutants) in different natural aquatic systems. Graphical abstract: Image 1 Highlights: Different fractions of DOM exhibited distinct binding capacity to As. Humic substance showed the strongest affinity to As. Microorganism metabolites was the main reason to bind As in eutrophic water. Cationic bridge was prone to occur in the presence of HSs other than protein. PO4 3− competed the binding sites with As.